1998
DOI: 10.1093/brain/121.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive process in preclinical phase of dementia

Abstract: Several recent prospective studies have demonstrated the existence of a preclinical stage of dementia, identifiable by neuropsychological assessment showing impairments with a great variety of cognitive tests. However, test scores are often colinear, largely because common cognitive components are involved in different tests; in spite of an apparent heterogeneity, it is still possible that a common cognitive component may be responsible for the deterioration shown in different tests in the preclinical phase. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
0
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(149 citation statements)
references
References 17 publications
7
137
0
5
Order By: Relevance
“…It was suggested that controlled processes (requiring attentional resources) are affected at an early stage while automatic processes are relatively more preserved (Jorm, 1986). The hypothesis of controlled processes impairment was explicitly explored in recent studies (Fabrigoule et al, 1998;Salthouse and Becker, 1998;Amieva et al, 2000). For example, Fabrigoule (1998) longitudinally studied cognitive performances in a large sample of 1,159 healthy elderly subjects.…”
Section: Controlled and Automatic Processes In Admentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that controlled processes (requiring attentional resources) are affected at an early stage while automatic processes are relatively more preserved (Jorm, 1986). The hypothesis of controlled processes impairment was explicitly explored in recent studies (Fabrigoule et al, 1998;Salthouse and Becker, 1998;Amieva et al, 2000). For example, Fabrigoule (1998) longitudinally studied cognitive performances in a large sample of 1,159 healthy elderly subjects.…”
Section: Controlled and Automatic Processes In Admentioning
confidence: 99%
“…Current features for dementia include a deterioration in cognitive functions, sufficient to impair daily living activities (APA, 1994). Neuropsychological studies have demonstrated that AD patients show impairment in controlled cognitive processes, while automatic activities may be more preserved (Fabrigoule et al, 1998). It is frequently observed that AD patients fail to consciously recollect information whereas they provide target memories in implicit conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We also expect a further and specific decrease of performance in AD patients (by comparison to healthy elderly subjects) on inhibitory tasks requiring controlled processes. Indeed, it is now well acknowledged that the various cognitive deficits presented by AD patients in the early stages of the disease are characterized by an impairment of controlled processes associated to a preservation of the automatic ones [1,38,87].…”
Section: Introductionmentioning
confidence: 99%
“…1 The results from this experiment shows evidence of this when the blind distance becomes wider. In this experiment, two interesting points were observed, one being the subject's ability to estimate the target more or less accurately in a blind area after memorizing the speed of the object.…”
Section: Discussionmentioning
confidence: 69%
“…While studies in areas of assessing were mainly concentrated on neuropsychological assessment measures which results varies across studies due to subjectivity, measuring the impairment directly in terms of units and numbers are not well studied and is difficult. 1 The purpose of this study was to investigate the decline in visual and cognitive abilities in young healthy individuals by comparing the results of two variables of the experiment namely; speed and blind distance. The cognitive function's outcome is a result of a higher intelligence in the working memory in the frontal lobe region.…”
Section: Introductionmentioning
confidence: 99%